Resistance to heavy metals and bioaccumulation of lead and zinc by Chryseobacterium solincola strain 1YB-R12T isolated from soil. (1st January 2014) - Benmalek, Yamina; Halouane, A.; Hacene, Hocine; Fardeau, Marie-Laure
A novel species of the genus Chryseobacterium which was isolated from soil, has been studied for resistance to heavy metals (lead, chromium, nickel, zinc, cadmium, copper and cobalt), antibiotic and its capacities for bioaccumulation of lead and zinc. It exhibited high minimal inhibitory concentration (MIC) values for metal ions tested ranging from 75 mg/l to 500 mg/l and antibiotic resistance to imipenem, cefuroxim, tetracyclin, nalidixic acid, fusidic acid, pipemidic acid, fosfomycin, cefalotin, dibekacin, furans and nitrofurantoin. The strain was able to accumulate more than 90% of lead and zinc during the active growth cycle. Study of pH effect on heavy metal removal indicated that the metal ion accumulation increased with increasing pH. Since Chryseobacterium solincola could grow at the presence of significant concentrations of toxic metals and because of its high metal accumulation capacity in aerobic conditions, may be potentially applicable in situ bioremediation of heavy metals contaminating aqueous or soil systems.